Biomimetic poly(glycerol sebacate) (PGS) membranes for cardiac patch application - Rai, Ranjana; Tallawi, Marwa; Barbani, Niccoletta; Frati, Caterina; Madeddu, Denise; Cavali, Stefano; Graiani, Gallia; Quaini, Frederico; Schubert, Dirk W.; Roether, Judith; Rosellini, Elisabetta; Boccaccini, Aldo R. (Materials Science and Engineering C, 2013)
In this study biomimetic poly(glycerol sebacate) PGS matrix was developed for cardiac patch application. The rationale was that such matrices would provide conducive environment for the seeded cells at the interphase with PGS. From the microstructural standpoint, PGS was fabricated into dense films and porous PGS scaffolds. From the biological aspect, biomimetic PGS membranes were developed via covalently binding peptides Tyr-Ile-Gly-Ser-Arg (YIGSR) and Gly-Arg-Gly-Asp-Ser-Pro (GRGDSP), corresponding to the epitope sequences of laminin and fibronectin, respectively onto the surface. To improve and enhance homogenous binding of peptides onto the PGS surface, chemical modification of its surface was carried out. A sequential regime of alkaline hydrolysis with 0.01 M NaOH for 5 min and acidification with 0.01 M HCl for 25 s was optimal. More COOH chemical group was exposed without causing deleterious effect on the bulk properties of the polymer as revealed by the physicochemical analysis carried out. HPLC analysis, chemical imaging and ToF-SIMS were able to establish the successful homogenous functionalization of PGS membranes with the peptides. Finally, the developed biomimetic membranes supported the adhesion and growth of rat and human cardiac progenitor cells.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.biomim
Keywords: Poly(glycerol sebacate); Cardiac patch; Biomimetic; Surface modification; Laminin; Fibronectin